Composite materials parts manufacturing - Fleischer, Jürgen; Teti, Roberto; Lanza, Gisela; Mativenga, Paul; Möhring, Hans-Christian; Caggiano, Alessandra (CIRP annals, 2018)
Composite materials parts manufacturing is based on the interactions of simultaneous as well as consecutive process steps. These influence the composite part properties and economical production. A wide range of possible composite materials and processing technologies necessitate a holistic view of the product life cycle to ensure the best possible economic and ecological outcome. Current studies on new manufacturing and machining processes aim for higher productivity and machinability, whereas new quality control approaches are enhancing the desired product quality. Furthermore, recent research addressing joining concepts and recycling methods has a huge impact on competitiveness and sustainability. Focusing on latest academic research approaches and current industrial application fields, this paper gives an overview of various process steps in the overall product life cycle of composite materials parts manufacturing.